Structural modification of Gum Arabic by β-galactosidase hydrolysis: Mechanism of saltiness enhancement and potential application in sodium reduction - Qiang Liu; Min Wang; Yufeng Zou; Zaifei Zheng; Yuting Hou; Jiakang Song; Tianlong Han; Dengyong Liu (Food Hydrocolloids, 2027)

Divergent controls on nitrogen and phosphorus export regimes across Chinese catchments - Xu Yang; Haojie Han; Xing Yan; Yuting Xie; Yanyu Ren; Yuhang Zhang; Daming Yang; Dongli She; Xuan Huang; Yongqiu Xia (Water Research, 2026)

Discovery of a novel Lactiplantibacillus phage enhancing flavor compound production in high-temperature Daqu - Yuhua Yao; Yabo Li; Meina Jiang; Yuting Sun; Xiaowei Zheng; Yansong Xue; Bei-Zhong Han (Food Microbiology, 2026)

What causes the summer surface ozone enhancement over the western Tibetan Plateau? - Yuting Sun; Chunhua Shi; Jian Rao; Lixin Han (Atmospheric Research, 2026)

Knockout of kdm4aa inhibits early embryonic development in zebrafish via downregulating cyp26a1 - Rui Deng; Xinqing Cai; Hui Jiang; Yuting Luo; Weiran Chai; Bingshe Han; Junfang Zhang (Molecular Genetics and Genomics, 2026)

Scalable nanoconfined GO/SWCNT-OH membranes for efficient high-salinity organic wastewater treatment - Yechen An; Xiaoxu Gao; Jing-Long Han; Yuting Ning; Xinping Fu; Ruiyun Ren; Liang Mei; Wenli Jiang; Ruifeng Yan; Jun Cui; Yu Tao; Aijie Wang (Water Research, 2026)

Interfacial-engineered dual-structured CuS/MoS2 composite photocatalyst with enriched active sulfur vacancies for efficient synergistic photothermal-photocatalytic removal of tetracycline - Xinhao Wang; Han Dong; Wenliang Liu; Yuting Lu; Xin Wang; Hui Li; Jiqian Wang; Dong Wang (Journal of Environmental Chemical Engineering, 2026)

Self-adhesive small intestinal submucosa-based hydrogel patch with dual-stage sequential curcumin release for pulmonary air leak sealing, sustained anti-inflammatory modulation, and lung regeneration - Yuting Cheng; Daping Yu; Zixun Wang; Bo Zhao; Pengfei Wei; Wei Jing; Yiqian Huang; Yuxin Guo; Huimin Li; Xuening Wang; Peng Jiao; Yandong Li; et al. (Chemical Engineering Journal, 2026)

Significant role of intermittent PMS backwash in mitigating irreversible fouling in MnTiO3 catalytic ceramic membranes - Guangxu Zhang; Jin Wang; Wubin Wang; Yadong Hu; Mengmeng Dou; Chao Han; Xinyu Li; Kaibo Wang; Yaxuan Liu; Yuting Ma (Journal of Water Process Engineering, 2026)

Mitochondrial genome and phylogenetic analysis of Aster Indicus L. - Ying Meng; Yuting Liang; Kaiyue Wang; Youjuan Zhu; Xinxin Zhao; Tong Zhang; Jingyu Yang; Fei Han; Juan Wang; Jiangtao Wu; Xiaofeng Shen (Genetica, 2026)

Integrated transcriptomic and metabolomic analyses reveal the differential response mechanisms of Gymnocypris eckloni gills to different intensities of acute heat stress - Wenzhuo Ban; Rongrong Liao; Yuting Duan; Mei Peng; Cheng Chen; RenYi Yang; Yinhua Zhou; ZhaoFang Han; Haiping Liu; Luo Lei; Chaowei Zhou (Journal of Thermal Biology, 2026)

An EGFR-directed photoimmunotheranostic conjugate enables tumor-specific imaging and potent synergistic antitumor activity - Tongshu Wu; Xinyu Cui; Yuting Tian; ZiHui Wang; Weijie Han; Dianlong Jia; Jun Li; Jinjie Chang (Journal of Photochemistry and Photobiology B: Biology, 2026)

Magnetotactic bacteria antagonized lead toxicity: Distinct detoxification mechanisms in magnetosome-containing/deficient bacteria - Ruoyun Dong; Yuting Ding; Han Li; Yanan Zhao; Yuanyuan Wu; Chenxi Zhou; An Xu; Yun Liu (Journal of Environmental Sciences, 2026)

Tibetan kefir grain fermentation remodels the water buffalo milk metabolome and enhances antioxidant and anti-inflammatory bioactivity in vitro - Jianmei Han; Ben Li; Yuting Wang; Chen Ding; Yafan Wan (Food Research International, 2026)

A novel Camellia oil microemulsion significantly enhances the bioaccessibility and antioxidant activity of curcumin: a comparative study with macroemulsion - Jingyi Chen; Jiayi Zou; Yuting Yang; Wei Li; Qihui Shui; Man Tian; Yu Zhou; Xingfa Han; Tao Chen; Lijun Zhou (Food Chemistry, 2026)

Universal primer-based RPA combined with parallel CRISPR/Cas12a decoding for rapid multi-species meat authentication - Shuang Han; Xinyi Lin; Yuting Lei; Zhen Liu; Jiayang Li; Xueling Ou (Food Chemistry, 2026)

A behavior-calibrated framework for prioritizing pesticide co-residue burdens in routine monitoring: Method development and a district-level pilot study in Shanghai - Bo Ding; Xiaoxing Lu; Hua Deng; Yuting Zhang; Junyi Shen; Ruobing Han; Jixing Yang (Food and Humanity, 2026)

Integrated Analysis of Physiological, Histological, and Transcriptomic Responses to Transport Density in Schizothorax nukiangensis - Jinlin Wang; Yuting Duan; Dapeng Gu; Hejiao Li; Luo Lei; Ning Wang; Wenjia He; Yinhua Zhou; Rongrong Liao; Mei Peng; Xinyu Liu; Zhaofang Han; et al. (Marine Biotechnology, 2026)

Label-free cell phenotypic profiling of sphingosine-1-phosphate receptor 1 and discovery of its agonist from natural products - Xiyi Wang; Yuchang Sun; Hongming Tang; Tao Hou; Han Zhou; Xiaomin Xie; Yuting Li; Pan Wang; Yang Han; Lai Wei; Fangfang Xu; Yanfang Liu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Neural network approach for predicting outcomes of external cephalic version for breech presentation: a retrospective cohort study - Yuting Xiang; Wenjian Yang; Haote Han; Haixia Lin; Wanhua Wu; Suran Huang; Hao Wang; Ning Hu; Zhongjun Li (Journal of Zhejiang University-SCIENCE B, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Exploring the oasis of plant genomes: From genetic variations to function and beyond - Xu Han; Zhanxiang Zong; Weidong Ning; Yuting Zhang; Zengdong Tan; Yunhao Liu; Yukun Song; Qiyuan Long; Yuyan Xiang; Shaoping Lu; Xuan Yao; Hu Zhao; et al. (Molecular Plant, 2026)

AI-driven monitoring strategy optimization for nutrient-polluted groundwater in a desert site in Northwest China - Yuting Yan; Yu Liu; Baocai Tong; Jinsheng Wang; Rui Zuo; Yuyu Wan; Yuanzheng Zhai; Xu Han (Journal of Hydrology, 2026)

Identification and rational engineering of a novel zearalenone-degrading enzyme from Fonsecaea erecta - Huimin Zhang; Laichuang Han; Magezi Joshua; Beihuang Huang; Yuting Jin; Songlin Zhang; Shiyi Yang; Minglong Shao; Zhiming Rao (Food Research International, 2026)

Molecular interactions of soy protein isolate with plant polyphenols: binding mechanisms and conformational insights - Jialong Han; Zihao Chen; Junhao Xia; Peiqi Peng; Jun Chen; Qin Geng; Xixiang Shuai; Yuting Liang; Taotao Dai (Food Bioscience, 2026)

Block-structured thermoplastic polycarbonate-based polyurethane films for perovskite solar cells: Enabling low-temperature encapsulation, high barrier properties, and tunable mechanical properties - Yuting Ouyang; Zihan Zhao; Min Xiao; Dongmei Han; Sheng Huang; Dongqin Bi; Shuanjin Wang; Yuezhong Meng (Chemical Engineering Journal, 2026)

Role of cholecystokinin (CCK) in reproductive regulation of female mandarin fish (Siniperca chuatsi) - Shuang Liu; Chongwei Wang; Yuting Wang; Chaowei Li; Jinmeng Teng; Suhan Peng; Jiaqi Lin; Jin Zhang; Haoran Lin; Linqiang Han; Ju Hu; Shuisheng Li; et al. (Aquaculture, 2026)

Cracking characteristics of rock-anchored beam system during construction of underground powerhouse under high in-situ stress and complex rock mass structures: A case study of Yebatan hydropower station - Peiyang Yu; Xiuli Ding; Shuling Huang; Xinhao Zhu; Yang Qin; Jianhua He; Yuting Zhang; Gang Han (Tunnelling and Underground Space Technology, 2026)

Clustering and entropy-guided unsupervised learning for multi-objective evolutionary optimization of reentrant hybrid flow shop scheduling - Chexiang Li; Yuyan Han; Yuting Wang; Qingda Chen; Fangzheng Gao (Swarm and Evolutionary Computation, 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

MnTiO3 catalytic ceramic membrane built and enhance PMS oxidation capacity: Experimental and theoretical calculation - Guangxu Zhang; Jin Wang; Mengmeng Dou; Wubin Wang; Chao Han; Yadong Hu; Xinyu Li; Kaibo Wang; Yaxuan Liu; Yuting Ma; Xin Zhang (Journal of Water Process Engineering, 2026)

Interpretable machine learning for exploring multiple influencing factors of PM2.5 and their interaction effects - Qiyuan Yang; Jie Gao; Jinxin Chen; Tong Ma; Han Xu; Feng Wang; Yuting Wei; Jinxing Liu; Qian Sun; Yinchang Feng; Guoliang Shi (Journal of Environmental Sciences, 2026)

Deformation Characteristics of Surrounding Rock in a Large Underground Opening Under High In Situ Stress and Complex Rock Mass Structures: A Case Study of Yebatan Hydropower Station - Peiyang Yu; Xiuli Ding; Shuling Huang; Peng-Zhi Pan; Yuting Zhang; Jianhua He; Ju He; Gang Han (Rock Mechanics and Rock Engineering, 2026)

Linking bacterial community assembly to soil carbon metabolism under different thermal regimens - Sen LI; Weigen HUANG; Han HU; Haowei NI; Jixian DING; Zhiyuan MA; Mengting Maggie YUAN; Jizhong ZHOU; Jiabao ZHANG; Yuting LIANG (Pedosphere, 2026)

Effects of geomorphic drivers and nutrient enrichment on periphyton nutrient retention in an urban stream: A multi-habitat comparative experiment - Ruzhong Li; Yuting Wang; Yang Fu; Chenyang Han; Lingxiao Qin (Limnologica, 2026)

Per- and polyfluoroalkyl substances in the environment and human tissue: A critical review of distribution, exposure pathways, and health risks - Zhenyu Zhang; Yuting Liu; Yi Chen; Han Qu; Jiaxue Ma; Mingyue Pang; Bin Wang; Gang Yu (Environmental Pollution, 2026)

Self-powered antimony oxide-coated palladium telluride/p-Silicon heterojunction DUV-MIR photodetector towards non-invasive diagnosis of diabetes - Jiayi Sun; Yuting Niu; Chen Rong; Zhikun Pang; Xinyi Han; Ningnuo Xiang; Lei Zhu; Xiaofang Li; Bo Peng; Cuicui Ling (Chemical Engineering Journal, 2026)

Metabolomics reveals GABA as a key mediator of salinity stress in razor clam - Geqi Gao; Zihan Lin; Yuting Han; Mengwei Shang; Jiahui Sun; Donghong Niu; Jiale Li (Aquaculture, 2026)

A systematic review of fault diagnosis methods for offshore wind turbines: Approaches, features, and emerging directions - Xinyan Wang; Runze Mao; Peihua Han; Ning Yuan; Yuanjiang Li; Yuting Guo; Shen Yin; Houxiang Zhang (Ocean Engineering, 2026)

HFPO-TA induces cardiac developmental damage in zebrafish by disrupting mitochondrial dynamics through FABP3 - Xing Liu; Mingzhu Xia; Xinyi Wu; Ruobing Chen; Yuting Peng; Yi Fan; Junjie Han; Yichun Zhao (Environmental Research, 2026)

Conservative Transport Using a Compact Third-Order Scheme on the Yin–Yang Grid - Juan Gu; Yuting Qiu; Xindong Peng; Xianbiao Kang; Han Jiao (Journal of Meteorological Research, 2026)

HGA-MPPO: A unified heterogeneous graph attention and multi-policy PPO framework for AGV-assisted flexible job shop scheduling - Xiaoyu Yang; Yuyan Han; Yuting Wang; Yuhang Wang; Leilei Meng (Swarm and Evolutionary Computation, 2026)

Anthracnose on Dioscorea nipponica caused by Colletotrichum spaethianum newly reported in China - Yuting Li; Jiaju Wu; Songhan Han; Lili Zhang; Naibo Yang; Yufei Chen (Physiological and Molecular Plant Pathology, 2026)

Dual effects of 6PPD at environmentally relevant concentrations on freshwater algae: Multi-omics reveals a shift in survival strategies from lipid-mediated adaptation to carbon-energy reallocation - Yuting Liu; Qin Fan; Bin Wang; Qiang Gao; Yi Chen; Xu Jing; Han Qu; Delin Qi; Mingyue Pang; Wei Wang (Journal of Hazardous Materials, 2026)

Development of a novel soybean protein isolate - rice bran wax bigel system: Effects of alternating electric field pretreatment and hydrogel/oleogel ratio on bigel properties - Yuting Wang; Ning Wang; Heqing Yang; Tong Wang; Cuiping Han; Dianyu Yu (Food Hydrocolloids, 2026)

Thioether and ether derivatives of diphyllin: synthesis and inducing tumor ferroptosis activity - Jianhang Han; Yujie Ma; Siwei Ji; Fan Yang; Qinyao Lu; Yuting Zhang; Yu Zhao (Natural Product Research, 2026)

The novel PFOS substitute OBS induces visual developmental toxicity in zebrafish embryos via ferroptosis - Xing Liu; Xinyi Wu; Mingzhu Xia; Yi Fan; Yichun Zhao; Junjie Han; Ruobing Chen; Yuting Peng; Man Qu (Toxicology Letters, 2026)

IP3K Knockdown Induces Oxidative Stress and Apoptosis in Sinonovacula constricta Under Low-Salinity - Yuting Han; Geqi Gao; Kai Ye; Donghong Niu (Marine Biotechnology, 2026)

Reducing the Discrepancy in Quantifying the Temperature Dependence of Global Wetland Methane Emission - Han Hu; Ke Xue; Yishen Sun; Qing Zhu; Hans K. Carlson; Ruiwen Hu; Rong‐Xi Tan; Chao Qian; Weigen Huang; Jizhong Zhou; Jingdong Mao; Thomas W. Crowther; et al. (Global Change Biology, 2026)
Understanding the apparent temperature dependence of wetland methane emissions ( E M ) is critical for predicting climate‐carbon feedbacks, yet current estimates remain constrained by observational limitations and methodological inconsistencies. The inherent biogeographic heterogeneity of wetland ecosystems combined with sparse, unevenly distributed flux measurements introduces substantial uncertainty in characterizing spatial patterns of E M . This knowledge gap impedes accurate projections of wetland methane contributions under climate warming scenarios. Here, we develop a framework that integrates mixed‐effects models with artificial intelligence techniques to resolve scale‐dependent patterns in methane emission thermodynamics across global wetlands. Our unified framework demonstrates that only 73.6% (5th–95th quantiles: 71.8%–75.4%) of the global wetland area conforms to classical Arrhenius‐type temperature dependence. This framework can predict 69.5% (67.9%–71.1%) of the global wetlands with high confidence using the Mahalanobis distance and area of applicability tests. We quantify the weighted mean E M across high‐confidence predictable areas of 0.694 eV, with latitudinal differentiation: tropical (0.634 eV), temperate (0.678 eV), and boreal (0.745 eV) wetlands exhibit progressively stronger temperature responses. Ignoring these biogeographic variations could result in underestimation of projected end‐century methane emissions by 4.2%–13.3% across selected socioeconomic pathway scenarios. Our study refined the temperature sensitivity parameter in coupled climate‐carbon cycle models, thereby enhancing predictive accuracy of future global warming trends and informing strategic responses to climate change mitigation.

Nomilin ameliorates perfluorooctanoic acid (PFOA)-induced impairment of zebrafish (Danio rerio) ocular development and visual function through PIK3CA activation - Xing Liu; Mingzhu Xia; Xinyi Wu; Ruobing Chen; Yuting Peng; Yi Fan; Junjie Han; Yichun Zhao; Man Qu (Toxicology and Applied Pharmacology, 2026)

A survey on Quality-Diversity optimization: Approaches, applications, and challenges - Haoxiang Qin; Yi Xiang; Hainan Zhang; Yuyan Han; Yuting Wang; Xinrui Tao; Yiping Liu (Swarm and Evolutionary Computation, 2026)

Genome-wide identification and functional characterization of rapid alkalinization factor 6 as a key peptide regulator of abiotic stress tolerance in Tartary buckwheat - Wenjun Sun; Yuxing Qin; Yuting Cao; Jianliu Tong; Linyuan Shi; Han Liu; Gujing Wang; Xiaoqin Zheng; Liang Zou; Liangzhen Jiang; Changying Liu; Dabing Xiang (Plant Science, 2026)

RAD51 m6A and PARylation modification orchestrate benzene-induced haematological toxicity - Lin Chen; Fengzhen Cui; Han Li; YuTao Zeng; Zhongming Wu; Weitian Chen; Qiaosheng Wen; Chunnian You; Yunqiang Xu; Lei Sun; Mingwei Sun; Qian Sun; et al. (Journal of Hazardous Materials, 2026)

Nomilin mitigates OBS-induced developmental cardiotoxicity via the Nrf2 pathway - Xing Liu; Yi Fan; Ruobing Chen; Yuting Peng; Xinyi Wu; Mingzhu Xia; Yichun Zhao; Junjie Han; Man Qu (Aquatic Toxicology, 2026)

Local Spatial Attention Transformer with First-Order Difference for Sea Level Anomaly Field Forecast: A Regional Study in the East China Sea - Yuting Wang; Hui Chen; Lifang Jiang; Qiyan Ji; Juan Li; Jianxin Wang; Guoqing Han (Journal of Marine Science and Engineering, 2025)
Accurate prediction of regional sea level anomaly (SLA) is critical for coastal hazard early warning, navigation safety, and infrastructure protection in economically active marginal seas such as the East China Sea (ECS), yet complex multiscale air–sea dynamics still make SLA forecasting challenging. This study proposes a Local Spatial Attention Transformer Network (LSATrans-Net) for short-term regional SLA prediction in the ECS, which incorporates a Local Spatial Attention mechanism designed for regional ocean processes and employs a first-order difference preprocessing strategy to reduce error accumulation induced by data non-stationarity. The LSATrans-Net outperforms ConvLSTM, BiLSTM, and CNN-Transformer in 7-day prediction experiments, with an RMSE of 0.017 m and a PCC of 0.984, with particularly strong forecasting skill in the ECS-Kuroshio and eddy-active regions. LSATrans-Net provides an efficient and physically interpretable framework for high-precision short-term SLA forecasting in dynamically complex marine regions, and offers reliable technical support for coastal disaster prevention and operational ocean forecasting systems.

Variations of source and aerosol composition over ten years: Implications for Clean Air Action Plan in a rapidly developing megacity - Yanqi Huangfu; Yingze Tian; Yuting Wei; Han Xu; Danlin Song; Fengxia Huang; Yinchang Feng (Journal of Environmental Sciences, 2025)

Chili-mediated aroma-taste interactions improve saltiness and umami perception in reduced-salt beef sauce - Qiang Liu; Min Wang; Zaifei Zheng; Zixuan Wang; Tianlong Han; Yuting Hou; Meilin Deng; Dengyong Liu (International Journal of Gastronomy and Food Science, 2025)

The threshold concentration capsaicin enhanced salty taste and reduced sodium: Sensory assessment and analysis of physiological and biochemical characteristics of saliva - Tianlong Han; Qiang Liu; Zixuan Wang; Min Wang; Yuting Hou; Shiyu Wang; Yuxuan Sun; Haixia Liu; Rui Chen; Dengyong Liu (Food Chemistry, 2025)

AgNWs/TPU based Joule heating and strain sensing yarn with temperature visualization through the coordinated regulation of multiple conductive pathways for physical exercise and health monitoring - Tao Yan; Xiaole Tao; Hong Lei; Yang Qiu; Zirui Han; Kaitai Wei; Bin He; Yuting Wu; Zhijuan Pan (Chemical Engineering Journal, 2025)

Cyclodextrin polyrotaxane based self oxygen supplying nanoparticles for enhancing the sonodynamic therapy mammary cancer performance with a “one-stone-two-birds” strategy - Yongyan Sun; Kaixuan Luo; Xi Zhu; Moxian Chen; Yuting Sun; Han Wang; Yunxiao Yang; Jianmei Yang; Guixi Wang; Jin Zhang; Jin Yan; Junnan He; et al. (Carbohydrate Polymers, 2025)

Application of feruloyl esterase BpFae03105 and xylanase XynAS Co-enzymolysis to produce ferulic acid from wheat bran - Han Lichun; Zhong Xiufang; Fu Zhilei; Yan Jinlong; Xiao Lin; Zhu Yuting; Liu Xiaoyan; Rana Abdul Basit; Wang Jinpeng; Yin Dafeng; Fan Guangsen (Biocatalysis and Agricultural Biotechnology, 2025)

Impacts of snow changes on hydropower potential under a changing climate - Ying Hou; Yuting Yang; Juntai Han; Ross Woods; Zihan Yan (Journal of Hydrology, 2025)

A tetrazole-based immunomodulator confers mitochondrial protection and enhances host resistance against IHNV in rainbow trout - Hui Zhang; Lili Zhu; Qinying Li; Hanwen Zheng; Yuting Dai; Xiaofeng Han; Guanglu Liu (Fish & Shellfish Immunology, 2025)

Redefining cyclodextrin-based systems: A multiscale framework of structure, function and application interconnection - Yu-han Zhang; Yuting Lin; Yihan Lin; Zheng Luo; Zibiao Li; Yun-Long Wu (Chemical Engineering Journal, 2025)

Deciphering the multifaceted effects of artificial sweeteners on body health and metabolic functions: a comprehensive review and future perspectives - Qiang Liu; Min Wang; Yuting Hou; Rui Chen; Haixia Liu; Tianlong Han; Dengyong Liu (Critical Reviews in Food Science and Nutrition, 2025)

Global terrestrial evaporation from physically-based, calibration-free complementary relationship - Zhuoyi Tu; Yuting Yang; Fangzheng Ruan; Changming Li; Juntai Han; Jinghua Xiong (Journal of Hydrology, 2025)

PDHA1-mediated H3K18 lactylation is involved in arsenic-induced nonalcoholic fatty liver disease by activating the CD36–NLRP3 inflammasome axis - Han Li; Zhenyang Li; Lin Chen; Xiaoshan Peng; Dapeng Wang; Qian Sun; Yuting Chen; Aihua Zhang; Qizhan Liu; Huanwen Tang (Journal of Hazardous Materials, 2025)

Quality enhancement and metabolic mechanism of fermented sausages with Lactiplantibacillus plantarum and Companilactobacillus alimentarius - Fangrui Han; Qiancheng Wu; Shan Li; Yuting Luo; Zengkang Ding; Tong Luo; Jiesong Liang; Chenxiang Fu; Yingchen Wang; Zhongjie Yu (Food Bioscience, 2025)

Nutrient-mediated changes in growth, biochemical composition, and biosilica deposition in Cyclotella cryptica - Yuting Yu; Yan Sun; Yuhang Li; Zhengfeng Zhu; Lin Zhang; Jian Li; Spiros N. Agathos; Chengxu Zhou; Jichang Han (Journal of Oceanology and Limnology, 2025)

A reinforcement learning-enhanced multi-objective Co-evolutionary algorithm for distributed group scheduling with preventive maintenance - Yanan Wang; Yuyan Han; Yuting Wang; Hongyan Sang; Yuhang Wang (Swarm and Evolutionary Computation, 2025)

Viral Diversity Mediates Carbon Allocation for Ecosystem Multifunctionality Across Biomes - Sen Li; Weigen Huang; Bin Ma; Longlong Xia; Han Hu; Yishen Sun; Haowei Ni; Mengting Maggie Yuan; Jizhong Zhou; Jiabao Zhang; Yuting Liang (Global Change Biology, 2025)
Viral diversity is essential for regulating the stability of ecosystem function by modulating the biochemical cycles via alterations in the survival and metabolic processes of host organisms. However, how viral survival strategies impact ecosystem function remains unresolved. Here, we analyzed 1824 metagenomes from soils across eight biomes, revealing that lytic viruses constituted a dominant proportion (88%) of the viral communities, with Siphoviridae (35.34%) being the most abundant lytic viral group. Viral communities significantly impacted soil organic carbon dynamics, while ecosystem multifunctionality was notably influenced by microbial necromass carbon, microbial biomass carbon, and various environmental factors. Microbial carbon use efficiency was the primary driver of ecosystem multifunctionality, with significant modulation by lytic and lysogenic viral communities, and lytic viruses contributed more directly to ecosystem multifunctionality (3%) compared to lysogenic viruses (1%). Our study underscores the pivotal role of viral communities, particularly lytic viruses, in shaping global carbon dynamics and ecosystem function, thereby providing a novel framework for future carbon management.

Corrigendum to “Design, hydrodynamic analysis, and test of a manta ray-inspired soft wing for flapping wing propulsion of underwater gliders” [Ocean Eng. 327 (2025) 120998] - Yudong Guo; Yuting Li; Xiao Yu; Libing Han; Wendong Niu; Tongshuai Sun (Ocean Engineering, 2025)

Digitally interactive smart textiles in football prepared by an outstanding viscose-based flexible strain sensor - Shidong Ma; Yuting Wu; Jian Tang; Jiayi Fu; Han Liu; Yumin Zhang; Jinyu Ma; Zhijuan Pan; Tao Yan (Chemical Engineering Journal, 2025)

Preharvest and Postharvest γ-Aminobutyric Acid Treatment Enhance Quality and Shelf Life in Strawberry (Fragaria × ananassa) Fruits - Ying Zheng; Xiaohuan Han; Yang Zhang; Weiwen Qiu; Tao Tao; Yuting Xu; Mohan Li; Xingbin Xie; Peipei Sun; Guanghui Zheng; Congbing Fang; Jing Zhao (Journal of Plant Growth Regulation, 2025)

Sex effects on dynamic structure–function coupling of intrinsic brain network - Xi Zhang; Dandan Li; Yuting Yuan; Xuebing Han; Lan Yang; Jiayu Lu; Ting Li; Zhifeng Li; Bin Wang (Brain Imaging and Behavior, 2025)

Tannin formaldehyde wood adhesives synthesized by photocatalytic degradation larch tannins to avoid the harm of formaldehyde - Wenjing Hu; Yuting Zhang; Ying Zhou; Yan Zhang; Shuguang Han (Journal of Hazardous Materials, 2025)

In-situ transformed bismuth titanate nanoarrays for mechanically driven degradation of formaldehyde under low-frequency airflow - Jun Han; Junhui Shao; Xingchen He; Najun Li; Yuting Qian; Dongyun Chen; Jianmei Lu (Journal of Environmental Chemical Engineering, 2025)

Control of sedimentary and diagenetic processes on the reservoir heterogeneity: A case study of the cretaceous carbonate reservoir in an onshore oilfield, Abu Dhabi - Yuting Peng; Yingxiao Fu; Hangyu Liu; Kaibo Shi; Bo Liu; Rubing Han; Xili Deng (Journal of African Earth Sciences, 2025)

The transcriptional factor MntR mediates hyperosmotic stress resistance by positively regulating the glycine betaine uptake system Gbu in Listeria monocytogenes - Yuting Yang; Yi Qin; Lanxin Tian; Minghao Zheng; Jinhua Xiao; Xu Han; Xiaowei Fang; Chun Fang (Food Bioscience, 2025)

A novel deacetylase inhibitor KLX suppresses liver fibrosis by deacetylating PPARγ through promoting ubiquitination-mediated HDAC1 degradation - Feng Zhang; Jinglun Song; Han Wu; Keying Lin; Chunlei Wang; Linghua Zeng; Xue Kong; Kunkun Zou; Hongtao Diao; Zhuo Wang; Wei Si; Weitao Jiang; et al. (Science China Life Sciences, 2025)

Design, hydrodynamic analysis, and test of a manta ray-inspired soft wing for flapping wing propulsion of underwater gliders - Yudong Guo; Yuting Li; Xiao Yu; Libing Han; Wendong Niu; Tongshuai Sun (Ocean Engineering, 2025)

Selective extraction of lithium from coal gangue utilizing a two-stage roasting process - Yu Xie; Zhengwei Han; Afsar Khan; Yuting Liang; Hui Zhong; Zhiguo He (Minerals Engineering, 2025)

Transcriptomic and Metabolomic Analyses Reveal Response Mechanisms of Sinonovacula Constricta to Saline-Alkalinity Stresses - Min Yang; Yuting Han; Yujie Chang; Chengbo Li; Donghong Niu (Marine Biotechnology, 2025)

Research progress of non-coding RNA regulating the role of PANoptosis in diabetes mellitus and its complications - Guangyu Han; Kaibo Hu; Tianfeng Luo; Wenting Wang; Deju Zhang; Liu Ouyang; Xiao Liu; Jianping Liu; Yuting Wu; Jianqi Liang; Jitao Ling; Yixuan Chen; et al. (Apoptosis, 2025)

Food waste behavior and neural response: an ERP study of Chinese urban residents - Yuting Jia; Xueyan Zhao; Caixia Hou; Mengmeng Zhang; Xiaoqi Wang; Xiaojie Zhang; Bin Han; Jiahua Li; Lu Sun (Environment, Development and Sustainability, 2025)

Enhancing Quality-Diversity algorithm by reinforcement learning for Flexible Job Shop Scheduling with transportation constraints - Haoxiang Qin; Yi Xiang; Fangqing Liu; Yuyan Han; Yuting Wang (Swarm and Evolutionary Computation, 2025)

Enhancement of rice production and soil carbon sequestration utilizing nitrogen-fixing cyanobacteria - Sen Li; Weigen Huang; Chengrong Peng; Xiaoyan Jing; Jixian Ding; Tong Chen; Ruilin Huang; Han Hu; Jizhong Zhou; Jiabao Zhang; Yuting Liang (Applied Soil Ecology, 2025)

A nationwide probabilistic risk assessment and a new insight into source-specific risk apportionment of antibiotics in eight typical river basins in China: Human health risk and ecological risk - Cong Men; Haoquan Jiang; Yuting Ma; Hengjiang Cai; Han Fu; Zifu Li (Journal of Hazardous Materials, 2025)

Insight into the sorption and desorption pattern of pyrrolizidine alkaloids and their N-oxides in acidic tea (Camellia sinensis) plantation soils - Yuting Lu; Haolei Han; Yuexing Yi; Yunfeng Chai; Chen Wang; Xiangchun Zhang; Xiangde Yang; Hongping Chen (Journal of Environmental Sciences, 2025)

AQP4- and Kir4.1-Mediated Müller Cell Oedema Is Involved in Retinal Injury Induced By Hypobaric Hypoxia - Cong Han; Yuting Li; Xingxing Zheng; Xiaoxia Zhang; Guonian Li; Liangtao Zhao; Zhaoqian Chen; Yi Yang; Wenfang Zhang (Molecular Neurobiology, 2025)

Effect of micro-granular activated carbon on bacteriophage MS2 removal and fouling control in flat-plate MBR - Yikan Zhao; Yingxue Sun; Yuting Han; Jiahao Li; Ning Ding; Toshiyuki Shibata; Qianyuan Wu (Environmental Research, 2025)

Multi-population coevolutionary algorithm for a green multi-objective flexible job shop scheduling problem with automated guided vehicles and variable processing speed constraints - Chao Liu; Yuyan Han; Yuting Wang; Junqing Li; Yiping Liu (Swarm and Evolutionary Computation, 2024)

The role of neuropeptide prothoracicotropic hormone (PTTH) - Torso in pyriproxyfen-induced larval-pupal abnormal metamorphosis in silkworms - Chunhui He; Yizhe Li; Zhenfeng Zhou; Yuting Wei; Yizhou Zhu; Yirong Han; Yifei Li; Rifeng Yang; Kaizun Xu (Pesticide Biochemistry and Physiology, 2024)

Biodiversity-safeguarding threshold for urea-fertilizer application on paddy fields: Protozoa-based toxicity tests - Chunyu Hou; Kexin Yu; Tianyi Shi; Benchao Jiang; Liangzi Cao; Wenyuan Wang; Mei Han; Jing Tang; Yuting Zhao; Xuming Pan; Jianye Li; Duu-Jong Lee; et al. (Journal of Environmental Management, 2024)

Triggering efficient redox cycling and electron transporting in CuCo spinel oxides via oxygen vacancy building for rapid degradation of antibiotics - Longlong Geng; Fengting Geng; Xianghan Cheng; Man Yang; Xiaoli Wang; Yong-Zheng Zhang; Da-Shuai Zhang; Xiuling Zhang; Wenyuan Han; Shujuan Zhuang; Yuting Chen; Guangzhi Hu (Chemical Engineering Journal, 2024)

Declining soil pH reduces microbial biomass-driven soil multifunctionality - Meitong Jiang; Weigen Huang; Jixian Ding; Zhiyuan Ma; Han Hu; Ruilin Huang; Yunfeng Yang; Jizhong Zhou; Yuting Liang (Applied Soil Ecology, 2024)

Sustainable and efficient recovery of lithium from rubidium raffinate via solvent extraction - Chenquan Ni; Chang Liu; Zhengwei Han; Jieyi Wang; Yuting Liang; Hui Zhong; Zhiguo He (Journal of Environmental Chemical Engineering, 2024)

Unraveling the Potential of Solid-State Hydrogen Storage Materials: Insights from First Principle Calculations - Yaohui Xu; Yang Zhou; Chaoqun Li; Shuai Dong; Hao Liu; Weijie Yang; Yuting Li; Han Jiang; Zhao Ding; Hao Li; Leon L. Shaw (Fuel, 2024)

Exploiting a tumor softening targeted bomb for mechanical gene therapy of chemoresistant Triple-Negative breast cancer - Yuting Shen; Xin Guan; Shaoyue Li; Xiaodong Hou; Jifeng Yu; Haohao Yin; Xuexia Shan; Xiaoxia Han; Lifan Wang; Boyang Zhou; Xiao Li; Liping Sun; et al. (Chemical Engineering Journal, 2024)

Lanthanum ferrite modified filling materials and its enhancement for phosphorus and COD removal: Performance and mechanism - Qing Li; Bei Yang; Xinyu Chen; Yuting Han; Qin Chen; Shiying He; Yanfang Feng; Yancan Wu; Xiaohui Liang; Lihong Xue; Jie Tang (Journal of Water Process Engineering, 2024)

The application of multi-point FBG bolt in measuring the excavation damaged zone of underground caverns - Gang Han; Shuling Huang; Xiuli Ding; Yuting Zhang; Jun He; Pengcheng Liu; Peiyang Yu; Dengxue Liu (Tunnelling and Underground Space Technology, 2024)

Theoretical analysis and methods of rapid evaluation: Solving the blocking flowshop group scheduling problem with the total flow time and total tardiness time criteria - Yuting Wang; Yuyan Han; Huan Li; Quan-ke Pan; Dunwei Gong (Swarm and Evolutionary Computation, 2024)

Volcanic lithofacies control the space in unconventional, rhyolitic hydrocarbon reservoirs: The Hailar Basin, NE China - Yuting Chen; Han Zheng; Guido Ventura; Linlin Zeng; Wei Pi; Yu Wei (Marine and Petroleum Geology, 2024)

Biothiols-activated near-infrared frequency up-conversion luminescence probe for early evaluation of drug-induced hepatotoxicity - Xiao Ma; Qingchun Lan; Shufen Pan; Yuting Han; Yi Liu; Yongquan Wu (Analytica Chimica Acta, 2024)

Disruption of PABPN1 phase separation by SNRPD2 drives colorectal cancer cell proliferation and migration through promoting alternative polyadenylation of CTNNBIP1 - Zhijie Hu; Mengxia Li; Yufeng Chen; Liutao Chen; Yuting Han; Chengyong Chen; Xin Lu; Nan You; Yawen Lou; Yingye Huang; Zhanfeng Huo; Chao Liu; et al. (Science China Life Sciences, 2024)

Intrinsic microbial temperature sensitivity and soil organic carbon decomposition in response to climate change - Sen Li; Manuel Delgado‐Baquerizo; Jixian Ding; Han Hu; Weigen Huang; Yishen Sun; Haowei Ni; Yanyun Kuang; Mengting Maggie Yuan; Jizhong Zhou; Jiabao Zhang; Yuting Liang (Global Change Biology, 2024)
Soil microbes are essential for regulating carbon stocks under climate change. However, the uncertainty surrounding how microbial temperature responses control carbon losses under warming conditions highlights a significant gap in our climate change models. To address this issue, we conducted a fine‐scale analysis of soil organic carbon composition under different temperature gradients and characterized the corresponding microbial growth and physiology across various paddy soils spanning 4000 km in China. Our results showed that warming altered the composition of organic matter, resulting in a reduction in carbohydrates of approximately 0.026% to 0.030% from humid subtropical regions to humid continental regions. These changes were attributed to a decrease in the proportion of cold‐preferring bacteria, leading to significant soil carbon losses. Our findings suggest that intrinsic microbial temperature sensitivity plays a crucial role in determining the rate of soil organic carbon decomposition, providing insights into the temperature limitations faced by microbial activities and their impact on soil carbon‐climate feedback.

Assessing the wastewater reclaim system consisted of wastewater plant - hybrid constructed wetland - ultra filtration and reverse osmosis in a chemical industrial park, a multi-criteria decision-making analysis - Huizhi Ding; Han Wang; Ganping Huang; Yuting Zhu; Lehua Zhang; Xiaolei Zhang; Min Zhou; Qiao Wang; Xiangying Li; Qixin Xu; Jun Zhao; Guangren Qian (Science of The Total Environment, 2024)

Interspecific occupancy-abundance relationship of benthic diatoms changes seasonally with attachment mode in a tropical river - Lin Tan; Yuting Liu; Muqi Shen; Guifeng Wei; Linglin Wan; Quehui Tang; Bo-Ping Han (Hydrobiologia, 2024)

Evaluation of ultimate biochemical carbon separation technology based on ultra-short sludge retention time activated sludge system - Yuting Shao; Han Zhang; Chongqing Xu; Guihuan Yan; Hongchen Wang; Guo-hua Liu; Lu Qi (Journal of Environmental Chemical Engineering, 2024)

Effect of dissolved organic matter on the inactivation of bacteriophage MS2 by graphitic carbon nitride - based photocatalysis - Yuqian Xie; Zhaoheng Zhang; Yikan Zhao; Yuting Han; Chen Liu; Yingxue Sun (Journal of Environmental Chemical Engineering, 2024)

MOFs-Based Materials for Solid-State Hydrogen Storage: Strategies and Perspectives - Yuting Li; Qifei Guo; Zhao Ding; Han Jiang; Hang Yang; Wenjia Du; Yang Zheng; Kaifu Huo; Leon L. Shaw (Chemical Engineering Journal, 2024)

Effect of sludge retention time on the removal of fluoroquinolone antibiotics in wastewater treatment of activated sludge - Yingxue Sun; Yuzhu Jiao; Mengyan Wang; Yikan Zhao; Yuting Han; Qianyuan Wu; Shibata Toshiyuki; Chun Wang (Journal of Water Process Engineering, 2024)

Study on the thawing characteristics of beef in plasma-activated water - Huixin Wang; Changjiang Ding; Jingli Lu; Yuting Bao; Bingyang Han; Jie Zhang; Shanshan Duan; Zhiqing Song; Hao Chen (Innovative Food Science & Emerging Technologies, 2024)

AaABCG20 transporter involved in cutin and wax secretion affects the initiation and development of glandular trichomes in Artemisia annua - Xueqing Fu; Han Zheng; Yuting Wang; Hang Liu; Pin Liu; Ling Li; Jingya Zhao; Xiaofen Sun; Kexuan Tang (Plant Science, 2024)

Exposure to particulate matter may affect semen quality via trace metals: Evidence from a retrospective cohort study on fertile males - Yuting Cheng; Jiaqi Zhu; Qiuqin Tang; Jing Wang; Jialin Feng; Yijie Zhou; Jinhui Li; Feng Pan; Xiumei Han; Chuncheng Lu; Xinru Wang; Marvin E. Langston; et al. (Chemosphere, 2024)

Unveiling the metal mutation nexus: Exploring the genomic impacts of heavy metal exposure in lung adenocarcinoma and colorectal cancer - Mengyuan Liu; Yuting Hong; Xiaohong Duan; Qiming Zhou; Jing Chen; Siyao Liu; Junyan Su; Li Han; Jiali Zhang; Beifang Niu (Journal of Hazardous Materials, 2024)

Redefining hybrid flow shop group scheduling: Unveiling a novel hybrid modeling paradigm and assessing 48 MILP and CP models - Yuting Wang; Yuyan Han; Quan-ke Pan; Huan Li; Yuhang Wang (Swarm and Evolutionary Computation, 2023)

Occurrence and fate of antibiotics and ARGs in a wastewater treatment plant with JHB process in Guangzhou, South China: Removal performance, interaction and host analysis - Yuepeng Deng; Huaihao Xu; Yuting Gu; Yongyin Lan; Junpeng Diao; Zhijian Xiao; Jiaming Zhu; Biqing Li; Jie Zou; Kaoming Zhang; Yuxian Liu; Jingchuan Xue; et al. (Journal of Water Process Engineering, 2023)

Simple synthesis of hierarchical Co-Meso-UTL zeolite for efficient epoxidation of styrene - Xue Liu; Zhongrui Wang; Tingyu Yan; Yulin Ma; Zhiguo Zhu; Xinqing Lu; Peng Han; Huiliang Li; Yuting Wang; Zejiang Liu; Sen Liu (Chemical Engineering Journal, 2023)

Overexpression of MbICE3 increased the tolerance to cold and drought in lettuce (Lactuca sativa L.) - Yangfan Wei; Zhenghao Li; Long Lv; Qian Yang; Zhi Cheng; Jiaqi Zhang; Wenhao Zhang; Yuting Luan; Aocheng Wu; Wenhui Li; Deguo Han (In Vitro Cellular & Developmental Biology - Plant, 2023)

Short-term prediction of the significant wave height and average wave period based on the variational mode decomposition–temporal convolutional network–long short-term memory (VMD–TCN–LSTM) algorithm - Qiyan Ji; Lei Han; Lifang Jiang; Yuting Zhang; Minghong Xie; Yu Liu (Ocean Science, 2023)
The present work proposes a prediction model of significant wave height (SWH) and average wave period (APD) based on variational mode decomposition (VMD), temporal convolutional networks (TCNs), and long short-term memory (LSTM) networks. The wave sequence features were obtained using VMD technology based on the wave data from the National Data Buoy Center. Then the SWH and APD prediction models were established using TCNs, LSTM, and Bayesian hyperparameter optimization. The VMD–TCN–LSTM model was compared with the VMD–LSTM (without TCN cells) and LSTM (without VMD and TCN cells) models. The VMD–TCN–LSTM model has significant superiority and shows robustness and generality in different buoy prediction experiments. In the 3 h wave forecasts, VMD primarily improved the model performance, while the TCN had less of an influence. In the 12, 24, and 48 h wave forecasts, both VMD and TCNs improved the model performance. The contribution of the TCN to the improvement of the prediction result determination coefficient gradually increased as the forecasting length increased. In the 48 h SWH forecasts, the VMD and TCN improved the determination coefficient by 132.5 % and 36.8 %, respectively. In the 48 h APD forecasts, the VMD and TCN improved the determination coefficient by 119.7 % and 40.9 %, respectively.

Uptake and translocation of organic pollutants in Camellia sinensis (L.): a review - Yuting Lu; Haolei Han; Xuchen Huang; Yuexing Yi; Ziqi Wang; Yunfeng Chai; Xiangchun Zhang; Chengyin Lu; Chen Wang; Hongping Chen (Environmental Science and Pollution Research, 2023)

Product maturation and antibiotic resistance genes enrichment in food waste digestate and Chinese medicinal herbal residues co-composting - Mengyu Cai; Guihan Dong; Yuting Zhou; Caiyun Yang; Hao Wu; Chunyu Guo; Haoran Zhang; Ying Han (Bioresource Technology, 2023)

Halophilic microalga-based circular economy producing functional food by reclaiming high-salinity seafood processing sewage - Yuting Chen; Chanyuan Song; Xinyu Cui; Jiakun Han; Kalyanee Paithoonrangsarid; Qinhua Gan; Yandu Lu (Biomass and Bioenergy, 2023)

A comparison of micro-flocculation and ozonation as pretreatments for ultrafiltration: organic removal and membrane fouling - Yujiao Li; Zhaoheng Zhang; Yikan Zhao; Yuting Han; Lanxin Ren; Yingxue Sun (Environmental Science and Pollution Research, 2023)

Effect of swelling pretreatment by coal tar on the microwave pyrolysis of waste tires - Zhanlong Song; Yuting Hu; Yuankai Han; Shouyan Chen; Xiqiang Zhao; Jing Sun; Yanpeng Mao; Xujiang Wang; Wenlong Wang (Journal of Environmental Chemical Engineering, 2023)

A magnetic biomass/MOF composite as a functional material for the oxidative removal of tetracycline: Degradation mechanism and toxicity study - Aaron Albert Aryee; Yuting Ma; Junli Wang; Runping Han; Lingbo Qu (Journal of Environmental Chemical Engineering, 2023)

Plastic bottles for chilled carbonated beverages as a source of microplastics and nanoplastics - Yalin Chen; Haiyin Xu; Yuanling Luo; Yuting Ding; Junguo Huang; Honghui Wu; Jianing Han; Linjing Du; Anqi Kang; Meiying Jia; Weiping Xiong; Zhaohui Yang (Water Research, 2023)

Profile and relaxation of sequence-specificity of DNA sulfur binding domains facilitate new nucleic acid detection platform - Yuting Shuai; Anan Xu; Jiayi Li; Zhaoxi Han; Dini Ma; Hairong Duan; Xinye Wang; Lan Jiang; Jingyu Zhang; Gao-Yi Tan; Xueting Liu; Yi-Lei Zhao; et al. (Science Bulletin, 2023)

Soft measurement and prediction of refrigerant leakage based on SVR-LSTM - Yuting Yang; Ling Xu; Hua Han; Zhengxiong Ren; Kongrui Wu; Feitian Liu (International Journal of Refrigeration, 2023)

Towards a universal evapotranspiration model based on optimality principles - Shen Tan; Han Wang; Iain. Colin Prentice; Kun Yang; Rodolfo. L.B. Nóbrega; Xiaomang Liu; Yong Wang; Yuting Yang (Agricultural and Forest Meteorology, 2023)

Different sensitivities and assembly mechanisms of the root-associated microbial communities of Robinia pseudoacacia to spatial variation at the regional scale - Yongli Ku; Xiaoting Han; Yuting Lei; Mei Zhang; Zhong Zhao (Plant and Soil, 2023)

Development of a low-density SNP genotyping panel by a novel technology mGPS and its application in germplasm identification of abalone - Weihong Lin; Qizhen Xiao; Feng Yu; Zhaofang Han; Junyu Liu; Wenzhu Peng; Zekun Huang; Yuting Lei; Weiguo Li; Weiwei You; Xuan Luo; Caihuan Ke (Aquaculture, 2023)

Soil tillage rather than crop rotation determines assembly of the wheat rhizobacterial communities - Tong Li; Huanxin Xie; Zhangheng Ren; Yuting Hou; Deqiang Zhao; Weiyan Wang; Ziting Wang; Yang Liu; Xiaoxia Wen; Juan Han; Fei Mo; Yuncheng Liao (Soil and Tillage Research, 2023)

Ultrathin metal organic framework nanosheets with rich defects for enhanced fluoride removal - Junyu Su; Maosen Yuan; Lu Han; Hongxia Deng; Jiahao Chang; Yuting Zhuang; Jinyi Wang; Yue Zhang (Chemical Engineering Journal, 2023)

Estimation of hourly actual evapotranspiration over the Tibetan Plateau from multi-source data - Xian Wang; Lei Zhong; Yaoming Ma; Yunfei Fu; Cunbo Han; Peizhen Li; Zixin Wang; Yuting Qi (Atmospheric Research, 2023)

Differential bone metabolism and protein expression in mice fed a high-fat diet versus Daurian ground squirrels following natural pre-hibernation fattening - Xuli Gao; Shenyang Shen; Qiaohua Niu; Weilan Miao; Yuting Han; Ziwei Hao; Ning An; Yingyu Yang; Yu Zhang; Han Zhang; Kenneth B. Storey; Hui Chang (Journal of Zhejiang University-SCIENCE B, 2022)

Linkage of vegetation and abiotic attributes to grazing effects on biogeographical patterns of arbuscular mycorrhizal fungal communities in temperate grasslands - An Yang; Wenwu Han; Yuting Li; Xueqin Zhang; Lulu Zhang; Meng Zhou; Lifei Ren; Qiuying Tian; Wen-Hao Zhang (Plant and Soil, 2022)

Cellulomonas triticagri sp. nov., isolated from the rhizosphere soil of wheat (Triticum aestivum L.) - Chuanyu Han; Yuting Zhang; Bing Yu; Qiqi Shan; Junwei Zhao; Haoran Shi; Yuanyuan Tian; Yan Zhang; Chunyu Zhu; Wensheng Xiang (Archives of Microbiology, 2022)

Coastal buoy observation of air-sea net heat flux in the East China Sea in summer 2020 - Yuting Han; Yangang Li; Changsan Xu; Lei Liu; Yanling Zhao; Wenqing Li; Xiangzhou Song (Journal of Oceanology and Limnology, 2022)

Enhanced genome editing to ameliorate a genetic metabolic liver disease through co-delivery of adeno-associated virus receptor - Shuming Yin; Lie Ma; Tingting Shao; Mei Zhang; Yuting Guan; Liren Wang; Yaqiang Hu; Xi Chen; Honghui Han; Nan Shen; Wenjuan Qiu; Hongquan Geng; et al. (Science China Life Sciences, 2022)

First report of Neovaginatispora fuckelii causing stem blight on Rosa chinensis in China - Yuting Han; Jianxin Chen; Jie Tang; Zejia Lv; Yuan Zheng; Huancheng Ma; Jianrong Wu (Journal of Plant Pathology, 2021)

A 168-year temperature recording based on tree rings and latitude differences in temperature changes in northeast China - Yangao Jiang; Yuting Cao; Junhui Zhang; Zhuo Li; Guoqiang Shi; Shijie Han; Cassius E. O. Coombs; Chuan Liu; Xiaoguang Wang; Junwei Wang; Lin Hao; Qi Xu; et al. (International Journal of Biometeorology, 2021)

Optimization of oil source correlation indexes: a case of Chang 10 member in Ordos Basin’ Zhoujiawan area - Kun Xu; Shijia Chen; Yuting Hou; Zixing Lu; Chen Li; Meimei Han (Arabian Journal of Geosciences, 2021)

Identification of glutathione transferase gene associated with partial resistance to Sclerotinia stem rot of soybean using genome-wide association and linkage mapping - Zou Jianan; Wenjing Li; Yuting Zhang; Wei Song; Haipeng Jiang; Jingyun Zhao; Yuhang Zhan; Weili Teng; Lijuan Qiu; Xue Zhao; Yingpeng Han (Theoretical and Applied Genetics, 2021)

Omega-3 fatty acid protects cardiomyocytes against hypoxia-induced injury through targeting MiR-210-3p/CASP8AP2 axis - Xueju Yu; Fengyao Liu; Yuting Liu; Bingqing Bai; Han Yin; Haochen Wang; Yingqing Feng; Huan Ma; Qingshan Geng (Molecular and Cellular Biochemistry, 2021)

Advanced glycation end-products suppress autophagy by AMPK/mTOR signaling pathway to promote vascular calcification - Yanyan Liu; Jing Li; Yuting Han; Yuying Chen; Lixuan Liu; Jiangli Lang; Chuan Yang; Hengcong Luo; Jie Ning (Molecular and Cellular Biochemistry, 2020)

Full genome sequence of a new mitovirus from the phytopathogenic fungus Rhizoctonia solani - Siwei Li; Yuting Li; Chenghui Hu; Chenggui Han; Tao Zhou; Can Zhao; Xuehong Wu (Archives of Virology, 2020)

Effects of straw and its biochar applications on the abundance and community structure of CO2-fixing bacteria in a sandy agricultural soil - Peipei Li; Wenju Chen; Yanlai Han; Daichang Wang; Yuting Zhang; Chuanfa Wu (Journal of Soils and Sediments, 2020)

A Binucleate Rhizoctonia anastomosis group (AG-W) is the causal agent of sugar beet seedling damping-off disease in China - Can Zhao; Yuting Li; Huajun Liu; Siwei Li; Chenggui Han; Xuehong Wu (European Journal of Plant Pathology, 2019)

Anastomosis group and pathogenicity of Rhizoctonia spp. associated with seedling damping-off of sugar beet in China - Can Zhao; Yuting Li; Siying Wu; Pinpin Wang; Chenggui Han; Xuehong Wu (European Journal of Plant Pathology, 2019)

Expression, purification, and evaluation of in vivo anti-fibrotic activity for soluble truncated TGF-β receptor II as a cleavable His-SUMO fusion protein - Xiaohua Wang; Yuting Li; Xin Li; Lei Yan; Huilin Guan; Ruijie Han; Yang Han; Jinqiu Gui; Xiaoyan Xu; Yan Dong; Haifeng Liu (World Journal of Microbiology and Biotechnology, 2018)

Retraction Note to: The Impact of Survivin on Prognosis and Clinicopathology of Glioma Patients: A Systematic Meta-Analysis - Shunzeng Lv; Congxin Dai; Yuting Liu; Ranran Shi; Zhenyu Tang; Mingzhi Han; Ruixiang Bian; Bowen Sun; Renzhi Wang (Molecular Neurobiology, 2017)

Assessment of the Association between Isocitrate Dehydrogenase 1 Mutation and Mortality Risk of Glioblastoma Patients - Yuting Dai; Xianbin Ning; Guoqian Han; Wei Li (Molecular Neurobiology, 2016)

RETRACTED ARTICLE: The Impact of Survivin on Prognosis and Clinicopathology of Glioma Patients: A Systematic Meta-Analysis - Shunzeng Lv; Congxin Dai; Yuting Liu; Ranran Shi; Zhenyu Tang; Mingzhi Han; Ruixiang Bian; Bowen Sun; Renzhi Wang (Molecular Neurobiology, 2015)

Cell Surface Protein C23 Affects EGF-EGFR Induced Activation of ERK and PI3K-AKT Pathways - Shunzeng Lv; Congxin Dai; Yuting Liu; Bowen Sun; Ranran Shi; Mingzhi Han; Ruixiang Bian; Renzhi Wang (Journal of Molecular Neuroscience, 2015)

Efficient Intracellular Gene Delivery Using the Formulation Composed of Poly (L-glutamic Acid) Grafted Polyethylenimine and Histone - Jingjing Deng; Yuting Wen; Cuifeng Wang; Shirong Pan; Huaiyu Gu; Xin Zeng; Lina Han; Yuefang Zhao; Min Feng; Chuanbin Wu (Pharmaceutical Research, 2011)